PENGEMBANGAN TUGAS MATEMATIKA DARING BERBASIS GOOGLE FORM PADA MATERI STATISTIKA DI KELAS VIII SMP/MTs - Atabik Rizqie (Jurnal Edukasi dan Penelitian Matematika, 2022)
Math's student’s assignment based on Google Form is one of the products that help students study by themselves. It is adapted from Learning Activities in the Grade 8 Mathematics Student Book. This product provides direct feedback to help students understand and avoid conceptual errors. This research aims to develop a valid and practical Google Form-based online math assignment on statistics material in class VIII SMP/MTs. The model used for this development research is Plomp model which consists of the Preliminary, Prototyping and Assessment Phases. The preliminary stage consists of needs analysis, student analysis, curriculum analysis and concept analysis. At the prototyping stage, the task is designed to produce prototype 1, then self-evaluation is carried out to obtain prototype 2. Furthermore, an expert review is carried out to get the validity of the product until a prototype 3 is obtained. Then a one-to-one evaluation is carried out to a group of students and the results are revised to obtain a prototype 4. Finally, prototype 4 was tested with a small group evaluation of nine students. The product can be accessed at https://linktr.ee/tugasmtk8statistika. The results showed that the product has a level of validity in the valid category and has a level of practicality in the practical category. The conclusion of   the resulting product is valid and practical. Keywords __ Student Assignment, Google Form, Online, Feedback, Student Book